2020
DOI: 10.1038/s41598-020-60097-0
|View full text |Cite
|
Sign up to set email alerts
|

Optically tunable terahertz chiral metasurface based on multi-layered graphene

Abstract: Active manipulation of the polarization states at terahertz frequencies is crucially helpful for polarization-sensitive spectroscopy, having significant applications such as non-contact Hall measurements, vibrational circular dichroism measurements and anisotropy imaging. the weakness of polarization manipulation provided by natural materials can be overcomed by chiral metamaterials. Chiral metamaterials have a huge potential to achieve the necessary polarization effects, hence they provide the basis for appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 61 publications
(51 reference statements)
0
28
0
Order By: Relevance
“…[19][20][21][22][23][24][25][26] Systems utilizing graphene could potentially provide the necessary functionalities. However, to achieve polarization conversion, symmetry breaking has to be introduced; this can be implemented geometrically, [15,[27][28][29] e.g., via patterned nanorectangles, [15] or by inducing anisotropy in the graphene conductivity, e.g., through the application of strong magnetic fields. [30] Alternatively, the tunable anisotropic conductivity of monolayer black phosphorus (BP), a 2D material with an inherent anisotropic crystalline structure, [24,31,32] can circumvent the above limitations, offering the desired tunability and wideband operation within the same system.…”
Section: Dynamic Control Of Light Chirality With Nanostructured Monol...mentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26] Systems utilizing graphene could potentially provide the necessary functionalities. However, to achieve polarization conversion, symmetry breaking has to be introduced; this can be implemented geometrically, [15,[27][28][29] e.g., via patterned nanorectangles, [15] or by inducing anisotropy in the graphene conductivity, e.g., through the application of strong magnetic fields. [30] Alternatively, the tunable anisotropic conductivity of monolayer black phosphorus (BP), a 2D material with an inherent anisotropic crystalline structure, [24,31,32] can circumvent the above limitations, offering the desired tunability and wideband operation within the same system.…”
Section: Dynamic Control Of Light Chirality With Nanostructured Monol...mentioning
confidence: 99%
“…prepared terahertz chiral metamaterials with polarization manipulation ability, which is constructed by multilayered graphene. [ 316 ] Hu et al. theoretically demonstrated that CD effects can be enhanced in chiral hybrid metamaterials composed of graphene and chiral metal nanocrystals at near‐infrared region.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Chiral metastructures are applicable platforms due to their chirality responses such as circular dichroism (CD) 1 and/or linear dichroism (LD) 2 in the terahertz (THz) region. Graphene-based chiral metastructures have been designed and developed recently to achieve tunable CD and/or LD chirality responses 1 6 . Graphene, 2D layer of graphite, with a thickness of 0.335 nm 7 , has become a promising material in electromagnetics and optoelectronics metastructures as it is capable of dynamically tuning electromagnetic waves 3 – 9 .…”
Section: Introductionmentioning
confidence: 99%